Identification of two novel HLA‐A alleles: A*24:199 and A*02:324. (26th July 2012) - Mantovani, M.; Frison, S.; Longhi, E.; Tagliaferri, C.; Mantia, M.; Piccolo, G.; Poli, F.
Summary Here, we describe two new HLA‐A alleles: A*24:199 and A*02:324. The two new variants are attributed to a single nucleotide mutation namely A→C for A*24:199 and G→A for A*02:324. Both point mutations are responsible for a change in translated amino acids.